You are on page 1of 5

International Mathematical Forum, 2, 2007, no.

12, 583 - 587

On K -algebras and BCI -algebras
M. Akram1 Punjab University College of Information Technology University of the Punjab, Old Campus Lahore-54000, Pakistan m.akram@pucit.edu.pk Hee Sik Kim Department of Mathematics Hanyang University, Seoul 133-791, Korea heekim@hanyang.ac.kr
Abstract In this paper we show that the K -algebra (G, ·, , e) on an abelian group (G, ·) is equivalent to the p-semisimple BCI -algebra (G; , e).

Mathematics Subject Classification: 06F35, 20A05. Keywords: K -algebra, BCI -algebra, p-semisimple, abelian group

1

Introduction

The notion of K -algebras on a group (G, ·) was first introduced by K. H. Dar and M. Akram in [1, 2] as a non-associative and non-commutative algebraic structure. A K -algebra was built on the group G(briefly, K(G)-algebra) by using the induced binary operation on (G, ·). Recently, K. H. Dar and M. Akram have proved that a class of K -algebras as a generalization of a class of B -algebras [10] and that of a family of BCH/BCI/BCK -algebras [6, 7, 8, 9] in [3]. In this paper we show that the K -algebra (G; ·, , e) is equivalent to the p-semisimple BCI -algebra (G; , e) whenever the group (G; ·) is an abelian but not an elementary abelian 2-group.
1

Corresponding author

u ∈ X . (C 3) x ∗ (x ∗ y ) = y . In BCI -algebras. A BCI -algebra (X . ∗. z. then (X . ∗. (C 2) 0 ∗ x = 0 implies x = 0. +) is an abelian group with identity 0 and x − y = x ∗ y . y. y. (C 4) x ∗ (0 ∗ y ) = y ∗ (0 ∗ x). the following hold: (B 5) (x ∗ 0) = x.3. Conversely.2. for any x. for any x. (B 4) x ∗ y = 0 and y ∗ x = 0 imply x = y . Proposition 2. 0) is said to be p-semisimple if X+ := {x ∈ X | 0 ∗ x = 0}. (C 5) (x ∗ y ) ∗ (z ∗ u) = (x ∗ z ) ∗ (y ∗ u) . let (X . if we define an addition “+” by x + y = x ∗ (0 ∗ y ) for any x. Proposition 2. (B 6) (x ∗ y ) ∗ z = (x ∗ z ) ∗ y . z ∈ X . . If we define x ∗ y := x − y . (B 2) (x ∗ (x ∗ y )) ∗ y = 0. For a BCI -algebra X the following are equivalent: (C 1) X is p-semisimple . then X+ = {0}. 0) is a p-semisimple BCI -algebra and x + y = x ∗ (0 ∗ y ) for any x. (B 3) x ∗ x = 0.1.584 M. y ∈ X . Akram and Hee Sik Kim 2 Preliminaries In this section we review some elementary aspects that are necessary for this paper. 0) of the type (2. then (X . (B 7) 0 ∗ (y ∗ x) = (0 ∗ y ) ∗ (0 ∗ x). In a p-semisimple BCI -algebra X . y ∈ X . +) be an abelian group with identity 0. By a BCI -algebra we mean an algebra (X . Definition 2. ∗.0) satisfying the following axioms: (B 1) ((x ∗ y ) ∗ (x ∗ z )) ∗ (z ∗ y ) = 0.

[1] A K -algebra (G. (e y ))) x. . x = x−1 . z = (23). e) on the symmetric group S3 = {e. y ∈ V2 (R). Define the operation on GLn (R) by A B = AB −1 . x. where (K1). 2. Then (G. and is given by the following Cayley table: e x y z a b e e x y z a b x x e b a z y y y a e b x z z z b a e y x a b z x y e a b a y z x b e Example 3. a. x = e. ·) in which each non-identity element is not of order 2 with the following axioms: (K1) (x (K2) x (K3) x (K4) x (K5) e y) (x (x z) = z y. z ∈ G. e = x. Then (G. If group (G. y) = y. e) is an algebra of the type (2. x (x y ) = x − (x − y ) = y . . then the axioms (K1 ) and (K2 ) are written as: (K1 ) (x (K2 ) x y) (x (x z ) = (x (e ((e y )) z) x. Let G = V2 (R) = {(x.1. B ∈ GLn (R).4. +. y . y. (K2). Example 3. y ) = (x Example 3. y = (13). b = (132). for all A. ·) is non-abelian . x = (12). [1] Consider the K (S3 )-algebra (S3 . x x = x − x = e. . ·. y ∈ R} be the set of all 2dimensional real vectors which forms an additive (+) abelian group. ·. .On K -algebras and BCI -algebras 585 3 K -algebras and BCI -algebras Definition 3. for all x. e) is a K -algebra. b. a = (123).3. . (K3). for all x. 0) defined on the group (G.2. ·. e) is a K -algebra. (x y ) (x z ) = (x − y ) − (x − z ) = z − y = z y . z } where e = (1). Define the operation on V2 (R) by x y = x − y . y ) : x. Let G = GLn (R) be the multiplicative group of all n × n real non-singular matrices.

. ·. .7. (a) (e (b) (x (c) e (d) x x) z) (e (e (e (y y) = y z) = x x=e y. g = e. y) = y (e x). +) is an abelian group and x − y = x y (see [4]). (B 4).9. y . ·. Corollary 3. . Theorem 3.8. (K 5) e x = e − x = −x. Conversely. Let g1 . ·) is not of order 2. e) is a p-semisimple BCI -algebra. for all x. The On the other hand. Then g1 g2 = e if and −1 = e in G. . (B 1). since (G. . . The p-semisimplicity (C 4) is equivalent to Proposition 3. . +) is an abelian group. By applying (K 1) and (K 3) we have ((x y ) (x z )) (z y ) = (z y ) (z y ) = e. Hence (G. i. (K 2) x (x y ) = x − (x − y ) = y . Proof. (B 3) ⇔ (K 3). for any x. ·. x e = x − e = x. Every element in a K-algebra is of order 2. z ∈ G. Proposition 3. e). Then by (K 4) and (K 2) we have x = x e = x (x y ) = y . then x) = x. Assume x y = e = y x. Hence g1 = g2 .8 and Meng’s observation [4] we conclude: Proposition 3. Thus (G. ·. By using Theorem 3. which is an inverse of x ∈ X . g2 ∈ G and g1 only if g1 = g2 . Then K -algebra (G. (K 4) x e = x − e = x. Let (G. e) be an abelian group. e x = e − x = −x. (K 1) (x y ) (x z ) = (x − y ) − (x − z ) = z − y = z y . ·) is equivalent to the p-semisimple BCI -algebra (G. Proof. By (K 2) and (K 3) we have (x (x y )) y = y y = e. Akram and Hee Sik Kim g2 ∈ (G. e) is a p-semisimple BCI -algebra. z R. e) on (G. assume that (G.5.7-(d). Let (G. . ·) be an abelian group such that each non-identity element of (G. ·. Then g1 g2 −1 = g1 g2 . g for all g ∈ G.. Suppose that g1 g2 = e. suppose that g1 = g2 . e) is a K -algebra on an abelian group G. (B 2). If we define x + y := x (e y ). (K5).6. Assume that (G. ·. (x y ). M. e) is a K -algebra. Then e = g1 g2 completes the proof. y. e). Then the following are equivalent: . [2] If (G.586 (K4). e) is a K -algebra. then (G. Lemma 3. Hence we can prove: (K 3) x x = x − x = e.e.

e) is a p-semisimple BCI -algebra and x ∗ y = x y. Characterization of a K (G)-algebras by self maps. 2005 . Japonica. Sci. On subclasses of K (G)-algebras. Dar and M. [5] C. Akram. Japan Acad. Straightforward. 11 (1983) 313-320. Imai. y ∈ G. Akram. On proper BCH -algebras. [6] Q. e) is a K -algebra. S. BCI -algebras and abelian groups. 32 (1987) 693-696. ∀x. 30 (1985) 659-661. 32 (1987) 749-756.29(1)(2005) 41-49. On axiom system of propositional calculi XIV . Proc. y ∈ G. P. Li. [3] K. Math. [9] K. On a K -algebra built on a group. Japan Acad 42 (1966) 26-29.On K -algebras and BCI -algebras 587 (i) (G. Hu and X. 28 (2004) 601-610. ∗. (iii) (G. [10] J. Math. Matematicki Vesnik . [4] J.. e) is an algebra where (G. S. H. +) is an abelian group and x + y = x (e y ). (ii) (G. Annals of University of Craiova. ·. Received: October 28. [8] Y. Math. BCI-algebras with condition(S). Meng. An algebra related with a propositional calculus. Akram. Seminar Notes. [2] K. Math. Dar and M. Iseki. Neggers and H. e) is an algebra where (G. 54(2002) 21-29. Kim. Japonica. Comp. and K. SEA Bull. H. SEA Bull. Hoo. P. 42(1966) 19-22. ·. References [1] K. Math. [7] Q. +. Math. . 33(2006) 1-6. Hu and X. ∀x. Math. Proof. ·. Iseki. H. On BCH -algebras. Dar and M. Ser. ∗. On B-algebras. Proc. Li . Japonica.